DIAGNOSTIC ACCURACY OF ULTRASOUND FOR SCREENING OF MACROSOMIA (The Research of Medical Science Review, 2025)
Introduction: Macrosomia poses significant maternal and neonatal risks, including prolonged labor, cesarean delivery, and birth trauma. In Pakistan, where limited healthcare resources and rising rates of obesity and gestational diabetes exacerbate the burden, timely detection is crucial. Ultrasound, as a non-invasive and cost-effective tool, offers potential for macrosomia screening in resource-constrained settings. Objective: To determine the accuracy of ultrasound findings for predicting the macrosomia among pregnant women who will be clinically suspected for macrosomia and referred to the radiology department for the ultrasound diagnosis of macrosomia presenting to the tertiary care setting for delivery, taking neonatal birth weight as gold standard. Methodology: This cross-sectional validation study was conducted at a tertiary care hospital of Islamabad from 6th July 2024 to 5th January 2025. A total of 155 female with age between 18-40 weeks having gestational age >36 weeks having singleton pregnancy and suspected for macrosomia on clinical examination and presented at term for delivery were selected for this study. Clinically Suspected Macrosomia was defined as the fundal height greater than 3 cm of the patient’s gestational age. Macrosomia on ultrasound was diagnosed by the Hadlock method. Macrosomia was confirmed through the fetal weight at the time of birth and neonate labelled macrosomic if weighs ≥4000 grams. Results: Ultrasound identified 43.9% (n=68) of cases as positive for macrosomia, while 32.9% were positive for macrosomia at birth. Among the cases identified as positive by USG, 29.0% (45/155) were true positive; while, those cases who were identified as negative by USG 52.3% (81/155) were true negatives. Sensitivity, specificity, PPV, NPV and overall accuracy of ultrasound for macrosomia screening was found as 88.2%, 77.9%, 66.2%, 93.1% and 81.3% respectively. Conclusion: The study demonstrates that ultrasound is a valuable screening tool for macrosomia, with high sensitivity and NPV. However, its moderate specificity and PPV highlight the need for cautious interpretation and integration with clinical assessment.